Effects of Digital Technology on Young People Ideologicaly Immunity - Bobur, Abdulhakimov (European Journal of Life Safety and Stability (2660-9630), 2022)
in this article the peculiarities of the modern age, in particular, the analysis of the relationship to their ideology. Also referred to as the age of internet and information technology to the effects of thinking about learning. In the article the impact of the virtual space of the mind and lifestyle of the problems of the modern age are studied at the same time, the essence of electronic culture, characteristics and development that appeared to age out the influence of the level of understanding of the approach is described. Immunity and the formation of the professional culture to the youth of this research, the effects of digitization the scale of effectiveness in determining the direction and about the importance of the word will go.